2019
DOI: 10.21873/invivo.11544
|View full text |Cite
|
Sign up to set email alerts
|

Combined EGFR/ALK Expression Analysis in Laryngeal Squamous Cell Carcinoma

Abstract: Background/Aim: Epidermal growth factor receptor (EGFR) acts as an oncogene in malignancies. Our aim was to examine the role of combined EGFR/ anaplastic lymphoma kinase (ALK) expression as molecular markers in laryngeal squamous cell carcinoma (LSCC) patients. Materials and Methods: Fifty (n=50) tissue sections derived from twenty-five (n=25) primary LSCCs were analyzed by immunohistochemistry (IHC). Results: EGFR overexpression was observed in 17/25 (68%) cases. Concerning ALK, 23/25 (92%) demonstrated low e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Another study group co-analyzing EGFR and KRAS mutations in Greek NSCLC patients detected a low-level mutational status, but KRAS mutations should be considered an independent prognostic factor that negatively affects prognosis in these patients (21). Similarly, another study showed that high co-expression of EGFR and another important molecule (anaplastic lymphoma kinase (-ALK) are associated with an aggressive biological behaviour (advanced stage/grade) in LSCCs (22). Concerning novel micro-genetic markers such as micro-RNAs, a study group showed that a specific variant allele in the KRAS 3' untranslated region involving the let-7 miRNA complementary site (KRAS-LCS6) is associated with aberrant KRAS expression.…”
Section: Discussionmentioning
confidence: 99%
“…Another study group co-analyzing EGFR and KRAS mutations in Greek NSCLC patients detected a low-level mutational status, but KRAS mutations should be considered an independent prognostic factor that negatively affects prognosis in these patients (21). Similarly, another study showed that high co-expression of EGFR and another important molecule (anaplastic lymphoma kinase (-ALK) are associated with an aggressive biological behaviour (advanced stage/grade) in LSCCs (22). Concerning novel micro-genetic markers such as micro-RNAs, a study group showed that a specific variant allele in the KRAS 3' untranslated region involving the let-7 miRNA complementary site (KRAS-LCS6) is associated with aberrant KRAS expression.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a previous study, we showed that EGFR overexpression is frequently detected combined with minimal ALK expression. Patients with OSCC demonstrating EGFR/ALK protein overexpression fulfill the genetic criteria for targeted therapeutic strategies (20).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning c-fos protein expression evaluation, we implemented a DIA protocol that provides an objective, accurate and fast mean for measuring the immunostaining intensity levels. According to our published experience in a variety of biomarkers, DIA is a useful tool for research and diagnostic reasons -under specific terms-enhancing the innovative evidencebased medicine [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%